Effectiveness of Exercise Treatments with or without Adjuncts for Common Lower Limb Tendinopathies: A Living Systematic Review and Network Meta-analysis - Dimitris Challoumas; Gearoid Crosbie; Seth O'Neill; Carles Pedret; Neal L. Millar (SpringerOpen, 2023)
Abstract Introduction Exercise therapy is usually prescribed as first-line treatment for lower limb tendinopathies. The multitude of exercise- and non-exercise-based management options can be overwhelming for the treating sports professional and patient alike. We chose to investigate the comparative effectiveness of exercise therapy with or without adjuncts for managing the commonest lower limb tendinopathies. Methods Through an extensive systematic literature search using multiple databases, we aimed to identify eligible randomised controlled trials (RCTs) on Achilles tendinopathy, patellar tendinopathy or greater trochanteric pain syndrome (GTPS) that included at least one exercise intervention in their treatment arms. Our primary outcomes were patient-reported pain and function (Victorian Institute of Sport Assessment; VISA). Follow-up was defined as short-term (≤ 12 weeks), mid-term (> 12 weeks to < 12 months) and long-term (≥ 12 months). The risk of bias and strength of evidence were assessed with the Cochrane Collaboration and GRADE-NMA tools, respectively. Analyses were performed separately for each one of the three tendinopathies. Results A total of 68 RCTs were included in the systematic review. All pairwise comparisons that demonstrated statistically and clinically significant differences between interventions were based on low or very low strength of evidence. Based on evidence of moderate strength, the addition of extracorporeal shockwave therapy to eccentric exercise in patellar tendinopathy was associated with no short-term benefit in pain or VISA-P. From the network meta-analyses, promising interventions such as slow resistance exercise and therapies administered alongside eccentric exercise, such as topical glyceryl trinitrate for patellar tendinopathy and high-volume injection with corticosteroid for Achilles tendinopathy were based on low/very low strength of evidence. Conclusion In this network meta-analysis, we found no convincing evidence that any adjuncts administered on their own or alongside exercise are more effective than exercise alone. Therefore, we recommend that exercise monotherapy continues to be offered as first-line treatment for patients with Achilles and patellar tendinopathies and GTPS for at least 3 months before an adjunct is considered. We provide treatment recommendations for each tendinopathy. PROSPERO registration number CRD42021289534.